A Model for Improving Public Service Performance Through Strengthening Digital Competence and Employee Engagement in Local Government Agencies - Lestari, Firda Maulani; Hadijah, Hady Siti (Universitas Padjadjaran, 2026)
This study examines the issue of lowquality public services in local governments, influenced by limited digital competence of civil servants and minimal employee involvement in work processes. This condition results in suboptimal service delivery, slow adaptation to technological developments, and a lack of responsiveness to community needs. This study aims to formulate a model for improving public service performance by strengthening digital competence of civil servants and increasing employee engagement as a driving factor for organizational change. The method used is a literature study spanning 2018–2025 with content analysis of various recent scientific sources discussing public services, digital transformation, and organizational behavior. The results show that digital competence of civil servants is still uneven, while the maturity level of e-government systems is mostly in the moderate category. Regions that implement digitalization in a planned manner have been shown to experience significant improvements in service quality. Furthermore, employee engagement plays a crucial role in supporting technological adaptation, accelerating work processes, and encouraging service innovation. Conclusion, the integration of strengthening digital competence, increasing employee engagement is a key prerequisite for local governments to realize more effective, fast, accurate, and responsive public services to the dynamics of community needs. The academic contribution of this study lies in the integration of digital competence and employee engagement within a comprehensive conceptual framework.